Is Human Security That Matters? An Analysis Of The Three-Year Report Of Jokowi's Administration On Human Security (HS) Perspective - Triwardani, Reny (POPULIKA, 2024)
In the third year of Jokowi's government, the focus remains on the continued economic transformation and the Indonesia-centric paradigm initially set in the first year. This study analyzes the three-year performance report of the Jokowi-JK government using the human security approach. The methodology involves a thorough review of reports and news on implementing equitable development. The study findings indicate that the Jokowi government has significantly prioritized development with a human security approach. Keywords: Human security; Nawa Cita Agenda; Indonesia-centric; Regionalized Development